A Systematic Synthesis of Critical Success Factors for Cybersecurity - Yeoh, William (2022)
Yeoh, W., Wang, S., Popovič, A., & Chowdhury, N. H. (2022). A Systematic Synthesis of Critical Success Factors for Cybersecurity. Computers and Security, 118(July), 1-17. [102724]. https://doi.org/10.1016/j.cose.2022.102724 -------------------------------The authors acknowledge the financial support from the Slovenian Research Agency (research core funding no. P5-0410).